SPLENIC INFARCTION: an intriguing and important cause of pain abdomen in high altitude - Hota, P. K.; Singh, K. J. (BALI MEDICAL JOURNAL; Vol 4 No 1 (2015), 2015)
Background: Patients with Sickle cell trait (SCT) are usually asymptomatic. They are usually unaware of their condition unless they have a family history. There are specific situations, where these people suffer from the effects of sickle cell trait. Splenic syndrome at high altitude is one of the specific problems. It is usually seen after a patient with SCT has been inducted to high altitude like in case of mountaineers and military personnel deployed in high altitude warfare. Pain abdomen due to splenic infarction in individuals with SCT is one of the manifestations. These patients, if diagnosed in time, they can be spared from unnecessary surgical interventions. We present herewith our experience of splenic infarction due to SCT in high altitude and their management.
Keywords: Splenic; infarction; Sickle cell phenomenon; Sickle cell trait; High altitude.